Psychiatrists' awareness of partial and nonadherence to antipsychotic medication in schizophrenia: results from an Asia–Pacific survey - Olivares JM (Dove Medical Press, 2013)
Jose Manuel Olivares,1 Manickam Thirunavukarasu,2 Jayashri Kulkarni,3 Hong Yan Zhang,4 Mingyuan Zhang,5 Fan Zhang61Department of Psychiatry, Hospital Meixoeiro, Complejo Hospitalario Universitario de Vigo, Vigo, Spain; 2Department of Psychiatry, SRM Medical College Hospital and Research Center, Tamil Nadu, India; 3Department of Psychiatry, Monash University and the Alfred Hospital, Prahran, Vic, Australia; 4Department of Psychiatry, Peking University Institute of Mental Health, Beijing, People's Republic of China; 5Department of Psychiatry, Shanghai Mental Health Center, Shanghai, People's Republic of China; 6Medical Affairs, Xian Janssen Pharmaceutical, Beijing, People's Republic of ChinaBackground: Nonadherence is a well-known problem among schizophrenia patients, among whom relapse is fivefold more likely, adversely affecting health, employment, and social functioning. The Spanish Adherencia Terapéutica en la Esquizofrenia (ADHES) survey was developed to determine the scope and causes of medication nonadherence in schizophrenia.Methods: The 20-question ADHES survey was distributed to 19,370 psychiatrists in 13 Asia–Pacific countries in January–April 2012, to ascertain psychiatrists' perceptions of antipsychotic medication adherence levels among their schizophrenia patients, reasons for partial/nonadherence, their preferred methods of assessing adherence, and strategies to improve adherence. Responses are reported as mean and range across countries.Results: Four thousand, six hundred sixty one psychiatrists (24% of recipients) completed the survey (highest contributors: People's Republic of China, 1854; India, 1616). Psychiatrists perceived that 56% (range, 30%-71%) of schizophrenia patients were non- or partially adherent to medication. Patients discontinue medication primarily due to lack of insight into their condition (mean, 37%; 1%–65%) and because patients consider medication unnecessary when feeling better (mean, 27%; 15%–68%). Over half of psychiatrists (mean, 55%; 42%–99%) assess medication adherence at every visit, almost exclusively (81%) by asking their patients, versus quantitative measures. One in three psychiatrists expressed their preference to switch to or add a long-acting antipsychotic to improve adherence (15%–82%).Conclusions: The substantial prevalence of partial/nonadherence to medication demonstrates that more proactive management of patients with schizophrenia is needed to improve adherence and thereby treatment outcomes.Registration: Registration of this study was not required.Keywords: schizophrenia, antipsychotic, APAC, survey, adherence